Furan resins as replacement of phenolic protective coatings: Structural, mechanical and functional characterization - Rivero, Guadalupe (2013)
Phenolic coatings are usually a convenient and economical way to protect metallic materials against wear and corrosion. Furan resins are analogous to phenolics, as they are obtained by replacing formaldehyde by furfural in their formulation. In this work, a furan resin based on furfural and phenol was synthesized and used as an aluminum coating. Thus, toxic emissions of formaldehyde were avoided, while a biobased derivative was used instead. The performance of the proposed resin was compared with the one of a traditional phenolic resin. Physicochemical characteristics including chemical structure, surface polarity and glass transition temperature were evaluated by means of Fourier transform infrared spectroscopy, contact angle measurements and dynamic-mechanical analysis, respectively. Nanomechanical and nanotribological properties were assessed by depth sensing indentation techniques. As well, the corrosion resistance of the furan coating was determined by potentiodynamic polarization tests. The obtained results validate the furan resin as a feasible alternative to phenolics to protect aluminum.